2021
DOI: 10.3390/antiox10030420
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Short-Chain-Fatty-Acid Resveratrol Esters and Their Antioxidant Properties

Abstract: To expand the applications and enhance the stability and bioactivity of resveratrol (RE), and to simultaneously include the potential health benefits of short chain fatty acids (SCFA) esters of RE were prepared by Steglich reactions with acetic, propionic, and butyric acids, respectively. RE and the esterified RE-SCFA products (including RAE, RPE, and RBE) were analyzed using nuclear magnetic resonance (NMR), Fourier-transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), differential thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…However, our previous study demonstrated that RBE does not cause cytotoxicity to HepG2, according to an MTT assay [ 39 ]. In addition, RBE can inhibit hydroxyl radical-induced DNA scission [ 40 ], which indirectly demonstrates the safety of RBE. For the sake of caution, the ADME of resveratrol and RBE (including resveratrol, resveratrol monoester 1, resveratrol monoester 2, and resveratrol diester) were evaluated using the SwissADME software, which is a free web tool for evaluating pharmacokinetics, drug-likeness, and medicinal chemistry friendliness, taking six physicochemical properties into account: lipophilicity, size, polarity, solubility, flexibility, and saturation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our previous study demonstrated that RBE does not cause cytotoxicity to HepG2, according to an MTT assay [ 39 ]. In addition, RBE can inhibit hydroxyl radical-induced DNA scission [ 40 ], which indirectly demonstrates the safety of RBE. For the sake of caution, the ADME of resveratrol and RBE (including resveratrol, resveratrol monoester 1, resveratrol monoester 2, and resveratrol diester) were evaluated using the SwissADME software, which is a free web tool for evaluating pharmacokinetics, drug-likeness, and medicinal chemistry friendliness, taking six physicochemical properties into account: lipophilicity, size, polarity, solubility, flexibility, and saturation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon completion of the reaction, a copious amount of distilled water was added, and the reaction mixture was filtered to obtain the precipitated RBE, which was freeze-dried and stored at −20 °C. The novel RBE was produced by the esterification of RSV and butyric acid, including RSV (about 17.11%), RBE monoester (47.12%), and RBE diester (35.00%) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacokinetic study reported by Huang et al (2019) showed that the blood concentration of RSV peaked within 0.5 to 2 h after oral administration, followed by a rapid decline [ 36 ], indicating that RSV is unable to induce adequate pharmacological responses in pregnant women; hence, it is not an ideal clinical drug. We reported novel resveratrol butyrate esters (RBEs) and indicated the esterification of RSV with butyrate that contained RSV (~17.1%), RBE monoester (~47.1%), and RBE diester (~35.0%), which also had better hydrogen peroxide scavenging activity than RSV [ 37 ] and could effectively inhibit fatty-acid-induced lipid accumulation in HepG2 cells, with effects similar to those of RSV, but achieved at a lower dose level [ 38 ]. Butyrate, one of the short-chain fatty acids (SCFAs), can selectively promote the growth of beneficial bacteria that improve the intestinal barrier’s function [ 39 ].…”
Section: Introductionmentioning
confidence: 99%